Energy savings in China's energy sectors and contributions to air pollution reduction in the 12th Five Year Plan. (1st November 2018) - Wang, Wenhuan; Tang, Xu; Yang, Xiaoguang; Zhang, Baosheng; Zhang, Yiqiong; Höök, Mikael
Abstract: Energy efficiency and air pollution mitigation are critical issues for future development of the Chinese economy. Energy savings and their contribution to reduced air pollution from energy sectors during the 12th Five Year Plan are assessed using input-output analysis. A new dynamic quantitative method was developed to explore key sectors and identify critical paths for efficient emission reductions from energy industries. All the energy intensive key sectors, including Metal, Power, Chemical Products, Nonmetal are used to determine critical paths for emission reductions. Results indicate that the Coal Sector failed to achieve significant energy savings and did not contribute to direct and overall emissions reductions. The Oil Sector only achieved co-effects for reduction of overall waste gas, SO2, and particulates, while the Power Sector achieved emission reductions of all air pollutants. The results suggest that Chinese government should enact four main measures to achieve effective targets for energy savings and emission reductions: (1) Strengthen energy conservation in Coal and Oil Sectors, particularly the Coal Sector. (2) Promote energy conservation and emission reductions in highly energy intensive sectors to help emission reductions from other sectors. (3) Promote synergy effects of energy savings and emission reductions to enterprises. (4) Set lowest emission reduction targets for each department combined with targets for energy savings. Highlights: Energy saving and synergetic air pollution reduction are assessed. A new quantitative method was used to identify key sectors and critical paths. Synergetic reductions were better in Power Sector than for other energy sectors. All critical paths of emission reduction include energy intensive sectors.